Effect of Different Complementary Feeding on Iron Deficiency Anemia and Growth in Breastfed Infants: Home-Made VS Commercial - Irawan, Roedi; Widjaja, Nur Aisiyah; Hanindita, Meta Herdiana (Folia Medica Indonesiana, 2019)
After approximately 6 months of age, term breastfed infants are increasingly depend on other sources of iron to avoid iron deficiency anemia, due to the depletion of the low concentration of iron in human milk. The appropriate complementary feeding must include a balance composition of foods containing an adequate amount of macro- and micronutrients to avoid iron deficiency anemia. This study aimed to compare the risk of iron deficiency and growth in breastfeed infants receiving commercial fortified complementary foods or home-made. A cross-sectional study was held on April-June 2016 to evaluate infants aged 6-24 months with breast feeding intake for 6 month of life. Complementary feeding practices were determined by questionnaire; an unquantified food frequency and feeding practices questionnaire was used to determine usual food intake. Biochemical assessment of haemoglobin (Hb), serum ferritin (SF) and serum iron (SI) level were measured. Anthropometric were assessed using WHO Child Growth Standard 2005. Statistical analysis used were Chi-square Test. Thirty eight infants were enrolled, mean age of 16.2 (SD 10.5) months. 17 infants consumed commercial complementary foods and 21 infants use home-made. Infants with home-made had lower Hb level, SF and SI than those receiving commercial complementary food, and had higher risk of underweight, stunted and wasted. Infants with home-made complementary food had lower haemoglobin, serum feritin and serum iron levels than those in fortified complementary food CF; and a higher risk of stunted and wasted than children with commercial fortified CF.